Comparative adaptogenic properties of Withania somnifera and Panax ginseng - Natarajan, Kanimozhi; Purushotham, Preethi M.; Rajendran, Aparnapreethi; Suresh, Swathika; Senthil, Kalaiselvi (Current Botany, 2022)
Adaptogens are natural (herbs) or synthetic compounds (levamisole) used to maintain stability in human body. The plant based adaptogens were mainly used to enhance the physical endurance and metal health of patients. However, adaptogens are widely studied for their ability to protect and cope up the body against physical, chemical and biological stress and related diseases. Panax ginseng and Withania somnifera are natural adaptogens, used to attenuate stress & related disorders without increasing oxygen consumption. This review deals with a detailed description of adaptogenic potential of Panax ginseng and Withania somnifera in improving human health. It also focuses on the similarity and mechanism of action of Panax ginseng and Withania somnifera as adaptogens on human stress induced disorders.